Exploration on the Integration Path of Short Videos and College Counselors' Ideological and Political Work - Tang, Li (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
With the rapid development of new media technology, short videos, featuring intuitive vividness, rapid dissemination, and strong interactivity, have become an important platform for contemporary college students to obtain information and exchange ideas. As the backbone force in carrying out ideological and political education for college students, college counselors are faced with the challenge that traditional ideological and political work methods do not match students' acceptance habits. By analyzing the communication characteristics of short videos and the current situation of college counselors' ideological and political work, this paper points out the necessity and existing problems of their integration, and further explores the integration paths from four dimensions: content creation, communication channels, interaction mechanisms, and team building. The purpose is to enrich the forms of ideological and political education, improve the pertinence and effectiveness of ideological and political work, and provide strong support for cultivating new talents who can take on the responsibility of national rejuvenation.